Natural and induced antibodies against phages in humans: induction kinetics and immunogenicity for structural proteins of PB1-related phages - Hodyra-Stefaniak, Katarzyna (2020)
Background: Bacteriophages may induce specific antibodies after natural exposure to phages or after phage therapy. As such, phage-specific antibodies might impact phage bioavailability in vivo, although limited non-neutralizing or insignificant effects have also been reported. Materials and Methods: Here, we report antibody induction against PB1-related phages (Pseudomonas viruses LMA2, F8, DP1) in mice over an 80-day period, for a healthy population of humans, and in patients undergoing phage therapy (oral and/or topical treatment). Results: All phages effectively induced specific immunoglobulin M and immunoglobulin G in mice. Phage-specific antibodies were observed in humans, whereas recombinant virion proteins (PB1 gp22, gp29) did not induce phage-neutralizing antibodies, either in mice or in humans. The healthy human population was differentiated for frequency of phage-neutralizing antibodies. Conclusions: These data can hold key considerations for phage therapy cocktail design, as highly similar phages can still be highly complementary in cases where specific immune response hinders therapeutic use of phages.